The super-scary sleepover - Quigley, Dawn (Quigley, Dawn. Jo Jo Makoons, 2025)
Spunky first grader Jo Jo Makoons knows a lot about bravery and boldness. Her cat, Mimi, is very brave when she tries new foods, and Teacher is very bold when he wears his ugly ties to school. When Jo Jo is invited to her first friend sleepover, it's her turn to be courageous! Only she's not quite sure how. Especially when scary puppets and dolls hide around every corner... Full of spooky fun and after-school mischief, the latest book in the Jo Jo Makoons chapter book series celebrates an Ojibwe girl with a big heart who finds her courage through the people she loves.